2018
DOI: 10.1177/1403494818756702
|View full text |Cite
|
Sign up to set email alerts
|

Is the environment in kindergarten associated with the vegetables served and eaten? The BRA Study

Abstract: Aim:The aim of the present study was to explore the associations between the economic, political, sociocultural and physical environments in kindergartens, along with the frequency and variety of vegetables served, and the amount of vegetables eaten. Method: The BRA Study collected data through two paper-based questionnaires answered by the kindergarten leader and pedagogical leader of each selected kindergarten, and a five-day vegetable diary from kindergartens (n = 73) in Vestfold and Buskerud Counties, Norw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 11 publications
(23 reference statements)
1
21
1
3
Order By: Relevance
“…Some previous studies have reported an association between food policies and children’s dietary intake [12,13]. Himberg-Sundet et al found that having their own written guidelines concerning the food and beverages that preschools offer to children was associated with a higher consumption of vegetables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some previous studies have reported an association between food policies and children’s dietary intake [12,13]. Himberg-Sundet et al found that having their own written guidelines concerning the food and beverages that preschools offer to children was associated with a higher consumption of vegetables.…”
Section: Discussionmentioning
confidence: 99%
“…Associations have been found linking food-related policies and regulations with the food and beverages served in childcare establishments [12], as well as with children’s dietary intake [13]. It appears that, in the US, healthier food is served to children in childcare centres that participate in the Child and Adult Care Food Program (CACFP) [14,15], which are more heavily regulated by the state and receive reimbursement for serving healthier food.…”
Section: Introductionmentioning
confidence: 99%
“…Baseline data were collected during Spring 2015, and follow-up I data were collected during Spring 2016. A detailed description of data collection has been published previously (20) . In brief, data were collected by paper-based questionnaires (one for kindergarten leaders, one for pedagogical leaders and one for assistants), and a 5-d weighted vegetable diary (filled in by anyone working at the department).…”
Section: Data Collectionmentioning
confidence: 99%
“…A detailed description of the 5-d weighted vegetable diary has been published previously (20) . Briefly, the kindergarten staff was instructed to weigh vegetables served for five consecutive days, both before and after each meal, and to report the number of children and adults present during the meal.…”
Section: -D Weighted Vegetable Diary: Amount Of Vegetables Servedmentioning
confidence: 99%
See 1 more Smart Citation